Pengaruh Electronic Word of Mouth di Instagram terhadap Brand Awareness Sisi Barat Cafe (Jurnal Ilmu Komunikasi dan Bisnis, 2022)
Instagram is a place and place that is widely used by young people to adults. There is a rapid increase in Instagram followers since the grand opening, the authors are interested in seeing whether there is an impact of electronic word of mouth on Instagram social media on brand awareness of shoppers at the West Side Cafe, and how much influence electronic word of mouth on Instagram has on consumer brand awareness. West Side Cafe to find out and how big the "Effect of electronic word of mouth on the West Side Cafe Account on Instagram on Consumer Brand Awareness" is a quantitative research strategy. This test uses quantitative research so that it can be seen the relationship between the two elements, namely specific electronic word of mouth on brand awareness. The result of the simple linear regression test obtained from processing information with the help of SPSS 25 is 1.109. So the results of this information can explain if the variable electronic word of mouth is considered constant (0), brand awareness is 1.109. While the regression coefficient on the electronic word of mouth variable is 1.216. The results obtained in processing information the coefficient of determination is 66%. After being assisted by SPSS 25, it can be said that there is an effect of electronic word of mouth on coffee brand awareness on the west side because the t count value is 26,892 and this result is more prominent than the t table worth 1,966 with an importance level of 0.000 < 0.05 then H0 is rejected and Ha is accepted. . So, the final result of the study describes